Analysis of spheroidized AISI 1050 steel in terms of cutting forces and surface quality - Baday, Şehmus; Başak, Hüdayim; Güral, Şehmus (REDAKCIA KOVOVE MATERIALY, 2016)
In this study, the effects of microstructure differences obtained with the application of different spheroidizing heat treatment cycles on medium carbon steel on cutting forces and surface roughness values were investigated. For this purpose, a group of AISI 1050 materials was annealed at 700 degrees C below A(c1). temperature for 720 min and cementite phases were spheroidized by the traditional method. Another group of materials was quenched after austenitization at 850 degrees C for 15 min and then cementites were spheroidized in the ferrite matrix by over-tempering separately at 600 degrees C for 15 and 60 min and at 700 degrees C for 60 min. Machining of the samples was tested under dry cutting conditions in CNC turning center with SNMG 120408 cementite carbide cutting tool and proper PSBNR 2525M12 tool holder with 75-degree edge angle. Cutting forces of traditionally spheroidized samples were lower than the samples spheroidized after quenching. In addition, their cutting forces decreased due to the increase in the average sizes of spheroidal cementite. Minimum surface roughness value was obtained from the samples which were spheroidized at 600 degrees C for 15 min after quenching. However, surface roughness rate of the sample increased as spheroidizing time increased.
Keywords: Spheroidizing; Cutting forces; Surface roughness; Medium carbon steel